The unusual widespread solar energetic particle event on 2013 August 19 Solar origin and particle longitudinal distribution - Rodriguez-Garcia L; Gomez-Herrero R; Zouganelis I; Balmaceda L; Nieves-Chinchilla T; Dresing N; Dumbovic M; Nitta NV; Carcaboso F; dos Santos LFG; Jian LK; Mays L; et al. (EDP SCIENCES S A, 2022)
Context: Late on 2013 August 19, STEREO-A, STEREO-B, MESSENGER, Mars Odyssey, and the L1 spacecraft, spanning a longitudinal range of 222 degrees in the ecliptic plane, observed an energetic particle flux increase. The widespread solar energetic particle (SEP) event was associated with a coronal mass ejection (CME) that came from a region located near the far-side central meridian from Earth's perspective. The CME erupted in two stages, and was accompanied by a late M-class flare observed as a post-eruptive arcade, persisting low-frequency (interplanetary) type II and groups of shock-accelerated type III radio bursts, all of them making this SEP event unusual.
Aims: There are two main objectives of this study, disentangling the reasons for the different intensity-time profiles observed by the spacecraft, especially at MESSENGER and STEREO-A locations, longitudinally separated by only 15 degrees, and unravelling the single solar source related with the widespread SEP event.
Methods: The analysis of in situ data, such as particle fluxes, anisotropies and timing, and plasma and magnetic field data, is compared with the remote-sensing observations. A spheroid model is applied for the CME-driven shock reconstruction and the ENLIL model is used to characterize the heliospheric conditions, including the evolution of the magnetic connectivity to the shock.
Results: The solar source associated with the widespread SEP event is the shock driven by the CME, as the flare observed as a post-eruptive arcade is too late to explain the estimated particle onset. The different intensity-time profiles observed by STEREO-A, located at 0.97 au, and MESSENGER, at 0.33 au, can be interpreted as enhanced particle scattering beyond Mercury's orbit. The longitudinal extent of the shock does not explain by itself the wide spread of particles in the heliosphere. The particle increase observed at L1 may be attributed to cross-field diffusion transport, and this is also the case for STEREO-B, at least until the spacecraft is eventually magnetically connected to the shock when it reaches similar to 0.6 au.